Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1021/acs.langmuir.6b02208
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Field Landscapes Guiding the Chemisorption of Diamagnetic Molecules

Abstract: It is shown that the self-assembly of diamagnetic molecule submonolayers on a surface can be influenced by magnetic stray field landscapes emerging from artificially fabricated magnetic domains and domain walls. The directed local chemisorption of diamagnetic subphthalocyaninatoboron molecules in relation to the artificially created domain pattern is proved by a combination of surface analytical methods: ToF-SIMS, X-PEEM, and NEXAFS imaging. Thereby, a new method to influence self-assembly processes and to pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Magnetic materials with engineered magnetic textures on micrometer length scales [1][2][3] have attracted attention due to their possible application in lab-on-a-chip devices [4][5][6][7], controlled self-organization [8,9], magnonics [10], controllable optically active surfaces [11] and biosensor applications [12]. One key limitation for lateral magnetic structures is the small feature size, leading to superparamagnetic fluctuations, and the lateral topography, which can limit accessibility by near contact techniques and provide an additional static potential landscape.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Magnetic materials with engineered magnetic textures on micrometer length scales [1][2][3] have attracted attention due to their possible application in lab-on-a-chip devices [4][5][6][7], controlled self-organization [8,9], magnonics [10], controllable optically active surfaces [11] and biosensor applications [12]. One key limitation for lateral magnetic structures is the small feature size, leading to superparamagnetic fluctuations, and the lateral topography, which can limit accessibility by near contact techniques and provide an additional static potential landscape.…”
Section: Introductionmentioning
confidence: 99%
“…The technique is based on magnetic textures engineered by light-ion irradiation of thin-film exchange bias systems in oriented applied magnetic fields. The three-dimensional stray field landscape emerging from magnetic charges in the topographically flat underlying material provides the ability to guide and manipulate magnetic particles and molecules over distances of several millimeters [6,9,13,[16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Local magnetic field gradients also find use in surface chemistry for controlling the position of adsorption of diamagnetic molecules. 6 These real-life applications call for an affordable and scalable fabrication process of large area nanomagnetic substrates with tunable stray field configuration and gradient.…”
Section: Introductionmentioning
confidence: 99%
“…Micro- and nanosized magnets are promising tools for manipulation, , sorting, and detection of biological samples or for applications in surface chemistry and sensor technologies . A review of recent advances in this broad and emerging research topic can be found in ref .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation